Komparasi Materi Bacaan Al–Qur'ān antara Riwāyat Hafş Ibn Sulaimān Al-Kūfīy dengan Riwāyat Warsy 'Uśmān Ibn Sa'īd Al-Mişrī dan Implikasinya pada Pembelajaran Baca Al–Qur'ān - S, Rizal Taufik (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study discusses the similarities and differences in Al-Qur'an reading material between riwāyat Hafş Ibn Sulaimān al-Kūfiy and riwāyat Warsy 'Uśmān Ibn Sa'īd al-Mişrī and its implications for Al-Qur'ān reading learning. In implementing this research process, methods are used that are in harmony with the object of research, so the author uses a type of library research and is descriptive, comparative, or content analysis. In line with the type and nature of research, the data sources that I use are primary data sources, in an effort to collect data using the Library Study method. Data analysis used is qualitative data analysis. Based on the results of the study show that there are similarities and differences in the reading material between riwāyat Hafş Ibn Sulaimān al-Kūfiy and riwāyat Warsy 'Uśmān Ibn Sa'īd al-Mişrī as well as its implications for Al-Qur'an reading reading, namely the similarity in pronouncing makhārij al-hurūf and şifat al-surat. However, there are differences in the form of verbs, iśbat, dialect differences (lahjah). Thus the difference in qirā'āt is caused by 2 (two) aspects, namely the historical aspect and the biological aspect. Implications for Al-Qur'an reading learning which includes components such as goals, material, methods, teachers and students, media and evaluation.